Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
2x^2 + 3x - 9 is = (2x- 3)(x + 3)
5x + 11 is = 5x + 11 bc u cant factor it.
-3x^2 + 1 is = -3x^2 + 1 because it cant factor.
- g(x) + h(x) is = x(-g + h)
Step-by-step explanation:
hope this helped lol
Answer:
-x^2-2x-19
Step-by-step explanation:
f(x)=(2x^2+3x-9) - g(x)=5x+11
First you must distribute the negative into g(x) so it would be g(x)=-5x-11
2x^2+3x-9-5x-11= 2x^2-2x-20
then you must add h(x) so...
2x^2-2x-20+(-3x^2+1)=
-x^2-2x-19
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.